Il “procedimento analogico” nei giuristi medievali e il “paradigma filosofico agostiniano”: Qualche breve nota per una ipotesi (Doctor Virtualis, 2023)
This essay means to put the spotlight on the role that analogy played in medieval jurists' modus operandi and modus arguendi, suggesting a multi-level reading of it as well, from the point of view of Il paradigma filosofico agostiniano (Parodi 2006).
Keywords: Argumentum a simili; Argumentum a contrario; Similitudo; Modus arguendi